MICRODISPLAY STRUCTURES BASED ON ORGANIC GREEN LIGHT EMITTING DIODES USING THERMALLY ACTIVATED DELAYED FLUORESCENCE MATERIALS - O. A. Grachev; E. F. Kudryashova; N. N. Usov (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The aim of the work is to develop a new highly efficient light-emitting structure of microdisplays based on organic light-emitting diodes (OLED) for the modernization of the microdisplayes MDO 02 of the mass production. It is also intended to use the new OLED structure in subsequent developments of new series of microdisplays, including a green glow. Сomplete microdisplay element consists of а active matrix and OLED structure, which is a set of layers of low molecular weight organic materials. The active matrix of the microdisplay MDO 02 contains 800×3(RGB)×600 pixels for the full-color version and 800×600 pixels for the monochrome version. Microdisplay MDO 02 has the following characteristics: the nominal brightness of the full-color glow is 140 cd/m2, the monochrome glow is – 560 cd/m2, the unevenness of the brightness is not more than 15 %, the contrast in relative units is not less than 100:1, the power consumption is not more than 450 mW, the operating time on refusal not less than 5000 hours. To improve these characteristics, it is proposed to use OLED structure, including materials with thermally activated delayed fluorescence (TADF). Materials with TADF have a much simpler synthesis scheme, an expanded selection of starting components and do not need expensive rare and rare-earth metals, which are used for the synthesis of phosphorescent materials. A structure with high light (external quantum yield up to 26.2 %) and electrical parameters with the described dopant synthesis process was selected from a number of OLED structure. This structure consists of four organic layers: hole-injection, hole-transport, emission and electron-transport. As a dopant for the emission layer, material aICTRZs based on indocarbosol derivatives was used. The dopant aICTRZs was synthesized by us according to the proposed synthesis method. The characteristics of this structure were evaluated using an ITO / TAPC (30 nm) / TCTA (10 nm) / CBP (25 nm) / Bphen (30 nm) / LiF (0.5 nm) / Al (150 nm). Although the optical characteristics of such an LED did not reach the declared values, they showed quite good results. As a result, such an OLED structure can be used as an initial one and, with its further development, one can count on stable and high results of the optical and electrical characteristics of MDs.